2019
DOI: 10.1088/1751-8121/ab05ec
|View full text |Cite
|
Sign up to set email alerts
|

Polymer collapse transition: a view from the complex fugacity plane

Abstract: Distributions of zeros of the grand canonical and canonical partition functions in the complex fugacity and in the complex interaction strength plane are examined numerically for a model of rooted self-interacting self-avoiding walks on a hierarchical graph. It is shown that the pattern of zeros of the grand canonical partition function in the complex fugacity plane has a circular-like form, with the exception of zeros lying in the vicinity of the critical point. Exact values of polymer size critical exponents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Almost all previous Y-L studies of collapse transition in lattice models of polymer physics were performed by examining behavior of zeros of a suitable canonical partition function [14][15][16][17][18][19], which is convenient for analyzing polymer thermal phase transitions. Recently, using an exactly solvable model of interacting self-avoiding walks [20], we have shown that study of grand canonical partition function zeros provides useful insights into geometrical critical behavior of the model, which allowed us to get very accurate estimates of size critical exponents in the swollen and compact polymer phases, as well as at the point of its collapse transition. Since the Y-L approach has also been very useful in studies of models of directed percolation [21,22], it is expected that similar analysis should be applicable to the case of directed animals as well.…”
Section: Introductionmentioning
confidence: 99%
“…Almost all previous Y-L studies of collapse transition in lattice models of polymer physics were performed by examining behavior of zeros of a suitable canonical partition function [14][15][16][17][18][19], which is convenient for analyzing polymer thermal phase transitions. Recently, using an exactly solvable model of interacting self-avoiding walks [20], we have shown that study of grand canonical partition function zeros provides useful insights into geometrical critical behavior of the model, which allowed us to get very accurate estimates of size critical exponents in the swollen and compact polymer phases, as well as at the point of its collapse transition. Since the Y-L approach has also been very useful in studies of models of directed percolation [21,22], it is expected that similar analysis should be applicable to the case of directed animals as well.…”
Section: Introductionmentioning
confidence: 99%